Exploring the Value of Dynamic Capabilities Theory: A synthesis of the theoretical building blocks - Breznik, Lidija (Naše gospodarstvo/Our economy, 2012)
As new sources of competitive advantage, dynamic capabilities emphasise specific aspects that were not the focus of attention in the previous strategy perspectives. The term dynamic refers to the capacity to renew resources and capabilities to achieve congruence with a changing business environment. The dynamic capabilities view has received lot of attention in recent years, although the outcome is a complex, sometimes confusing body of research. In this paper, we present a synthesis of the origins and ideas on which the theory was built. Our purpose is to draw attention to the promising avenues and the potential offered by the dynamic capabilities view in order to encourage further development. By introducing the terminology into Slovenian practice, we expand the possibility of improving it.